Efficient reverse click labeling of azide oligonucleotides with multiple alkynyl Cy-Dyes applied to the synthesis of HyBeacon probes for genetic analysis - Gerowska, M; Hall, L; Richardson, J; Shelbourne, M; Brown, T (2012)
A convenient method of oligonucleotide labeling using click chemistry has been developed. A 2′-mesyloxyethyl ribothymidine phosphoramidite monomer was incorporated into DNA at several loci during solid phase oligonucleotide synthesis and converted to 2′-azidoethyl ribothymidine in high yield on the synthesis resin. The resultant azide oligonucleotides were doubly and triply labeled with alkyne-modified cyanine dyes and their biophysical properties were studied. The influence of the dye structures and method of labeling on the fluorescence properties of the DNA probes is discussed and compared with a standard labeling method using active esters of Cy-Dyes. © 2011 Elsevier Ltd. All rights reserved.